PineBaby : Organic liquid cleanser formulated using bromelain from pineapple byproducts - Aizi Nor Mazila, Ramli; Muhammad Raziq Zikry, Mohammud; Nur Farah Syazni, Norsazali; Aimi Wahidah, Aminan (2021)
PineBaby organic liquid cleancer is responsible as cleaning agents that help to remove milk fats and spot dirt on the feeding bottles, toys and baby accessories without any affect on the equipment surface and its functionality. PineBaby organic liquid cleanser is formulated using plant based and biodegradable ingredients and effectively kills 99.9% of bacteria. Baby care from day 1. Pineapple by products (stem, core, crown and peel parts) source of proteolytie enzyme (bromelain). Higher demand in pineapple industry huge pineapple by products generations.